Screening of Korean Natural Products for Anti-Adipogenesis Properties and Isolation of Kaempferol-3-O-rutinoside as a Potent Anti-Adipogenetic Compound from Solidago virgaurea - Young Soo Jang; Zhiqiang Wang; Jeong-Min Lee; Jae-Young Lee; Soon Sung Lim (Molecules, 2016)
In this study, the anti-adipogenetic activity of 300 plant extracts was investigated using an Oil Red O staining assay in a 3T3-L1 cell line. Our results indicate that three plants, including the stem and leaf of Physalis angulata, the whole grass of Solidago virgaurea, and the root of Dioscorea nipponica, produced over 90% inhibition of adipogenesis. Kaempferol-3-O-rutinoside, which demonstrated a 48.2% inhibitory effect on adipogenesis without cytotoxicity, was isolated from the butanol layer of a water extract of S. virgaurea guided by the anti-adipogenesis assay in 3T3-L1. PPAR-γ and C/EBPα expression levels were determined using western blot, and our results indicate that kaempferol-3-O-rutinoside has a strong anti-adipogenic effect in 3T3-L1 cells through the suppression of increases in PPAR-γ and C/EBPα expression.